GAMBARAN PENGETAHUAN PERAWAT PUSKESMAS DENGAN TINGKAT KETERLAKSANAAN KEGIATAN PERKESMAS DI KECAMATAN RAPPOCINI KOTA MAKASSAR - Ibrahim, Hajaratul Azwaningsih; Ilmi, Ani Auli; Hasnah, Hasnah (Journal of Islamic Nursing, 2017)
Community health care activities (Perkesmas) is a clinic program which is integrated activities in computsory health efforts as well as health development efforts. This study aims to find out the description of the knowledge of clinic nurse with level implementation of communityhealth care activities in Rappocini district Makassar city. The research design use is descriptive research type with cross sectional approach with number of samples 30 respondents using non probability sampling technique. Data collection use questioner. Data analysis using chi-square test. The result show that the respondents who have good knowledge of 73,3% and respondents who have the level of implementation optimal perkesmas activities by 80%. The result of chi-square test stowed that there was a correlation between the clinic nurse knowladge with the level implementation of community health care activity (p= 0,013). This research recommends to clinic nurse in order to take an active role in participating in training of public health officer to increase their ability in conducting the activity of health center.